Design and Performance Evaluation of A Portable Low-Head Pico-Hydro System using A Rewound Axial Generator for Rural Energy - Aripriharta, Aripriharta; Nibrosoma, Ahmad Dhaffa; Afandi, Arif Nur; Faiz, Mohamad Rodhi; Rahmadhani, Nur Aini Syafrina; Bagaskoro, Muhammad Cahyo; Rosmin, Norzanah (P3M Politeknik Negeri Banjarmasin, 2025)
This study evaluates the performance of a pico-hydro system installed on a river with low head and discharge. The system was assessed under no-load and varying load conditions (25–100%). The results indicate that the generator performs according to the initial design, despite some fluctuations in output parameters. Under no-load conditions, the generator maintains a stable output voltage between 12–14 VAC, with a rotational speed of 590–600 RPM, a system frequency of 59–60 Hz, and zero current. The step-up transformer successfully raises the voltage to 220–222 V with high stability, although minor ripple is observed in the output signal. Under load, the generator voltage slightly decreases to 12–14 V as the load increases. The rotational speed also declines (560–590 RPM), affecting frequency stability, which drops from 59 Hz at 25% load to 56 Hz at full load. The current rises proportionally with the load, from 0.10 A at 25% to 0.45 A at 100%. The observed performance drop under load highlights the effect of load on generator speed and overall system output. The primary impacts of the 25–100% load range are evident in generator speed, frequency stability, and waveform quality. Overall, the system performs satisfactorily for low-head pico-hydro applications with a power capacity of up to 100 Watts, suitable for rural street lighting.